Increasing the Ability to Understand Mathematical Concepts through the Team Games Tournament (TGT) Model Assisted by the PhET Application - Putri, Sarah Anida; Rohimah, Siti Maryam; Nurhadi, Moh (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2024)
This research aims to determine the increase in the ability to understand mathematical concepts in grade III elementary school students through the Team Games Tournament (TGT) learning model assisted by the PhET application and conventional learning models. The method used is a quasi-experimental design and a nonequivalent control group design. Participants in this research were 63 grade III elementary school students. Sampling in this study used a purposive sampling technique. Data collection techniques in this research are tests, observation, interviews, and documentation. The instrument used consists of a test of the ability to understand mathematical concepts in the form of a description and is stated to have met the requirements for content validity, construct validity, reliability, level of difficulty, and differentiation. The data analysis technique for hypothesis testing uses IBM SPSS Statistics 2.6 software, namely the normalized n-gain hypothesis test. Based on the research results, students' ability to understand mathematical concepts at SDN Pancasila Lembang experienced a significant increase after receiving learning using the Team Games Tournament (TGT) learning model assisted by the PhET application. This is proven by the results of the n-gain data test calculation, which is 0.36 in the medium category. The average posttest score obtained for the experimental class was 67.78 and the average posttest score obtained for the control class was 30.32. This means that the increase in understanding of mathematical concepts in the experimental class is higher compared to the control class. Therefore, it can be concluded that the Team Games Tournament (TGT) learning model assisted by the PhET application is recommended as an alternative learning model for improving students' ability to understand mathematical concepts in elementary school.